Access to a stereoisomer library of solomonamide macrocycles - Jachak, Gorakhnath R.; Athawale, Paresh R.; Choudhury, Rahul; Kashinath, K.; Reddy, D. Srinivasa (Chemistry-An Asian Journal, 2019)
In an attempt towards understanding stereo-structure activity relationships (SSARs), we have prepared eight possible stereoisomers of solomonamide macrocycles, in particular, by changing the stereochemical pattern of non-peptide fragment AHMOA. Here, we have demonstrated different ways to construct three contiguous chiral centers present in solomonamide B macrocycle using substrate/reagent-controlled methods. These methods involve Brown crotylation, NHK reaction and Evans aldol addition as key steps to synthesize key non-peptide fragment. Further, these non-peptide fragments were converted to their corresponding macrocycles via ligand-free intramolecular Heck reaction.
Keywords: Crotylation; Heck reaction; Inflammation; Macrocycles; Stereochemistry

Total synthesis and absolute configuration determination of Ktedonoketone, a benzenoid metabolite from Thermophilic bacterium - Dandawate, Monica; Choudhury, Rahul; Krishna, Gamidi Rama; Reddy, D. Srinivasa (Tetrahedron Letters, 2020)
The successful total synthesis of both enantiomers of ktedonoketone allowed us to decipher an unambiguous assignment of absolute configuration of the natural product. The concise synthesis highlights Wacker oxidation and aldol condensation as key steps. In addition to this, the current synthetic route is suitable to access a library of compounds on the similar skeleton as one can use readily available amino acids and Grignard reagents as variants. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Absolute configuration; Ktedonoketone; Total synthesis; Wacker oxidation

Separation of a diastereomeric diol pair using the mechanical properties of crystals - Gamidi, Rama Krishna; Dandawate, Monica; Choudhury, Rahul; Tothadi, Srinu; Nangia, Ashwini; Reddy, D. Srinivasa (Crystengcomm, 2021)
We report the separation of a (2S,3R/S)-3-ethyl-1-phenylhex-5-ene-2,3-diol (ephd) diastereomeric pair with visually indistinguishable acicular morphologies based on their mechanical responses, which is found to be more efficient than conventional separation methods. Furthermore, the molecular crystals of (2S,3R)-ephd show elastic deformation, while (2S,3S)-ephd fractures in a brittle manner under similar conditions.

Total synthesis of a hypothetical macroketone of migrastatin - Choudhury, Rahul; Reddy, D. Srinivasa (European Journal of Organic Chemistry, 2021)
Danishefsky's macroketone, a simplified analogue of natural product Migrastatin, is one of the lead compounds with potent cancer cell migration inhibition potential. Different biological assays suggest fascin protein as the potential target. Although it was indicated through X-ray co-crystallography where the concerned macroketone analogue was found to bind in the actin-binding sites of fascin, there was a structural discrepancy, as the X-ray co-crystal structure suggested an E-olefin along with inversion of methyl stereochemistry from that of Danishefsky's macroketone. Here, we have accomplished the total synthesis of the `hypothetical macroketone' for the first time. The TiCl4 mediated vinylogous Mukaiyama aldol reaction is the key step in present synthesis.
Keywords: Hypothetical mecroketon; Metastasis; Migrastatin; RCM; vinylogous Mukaiyama aldol reaction (VMAR)

Kupyaphores are zinc homeostatic metallophores required for colonization of Mycobacterium tuberculosis - Mehdiratta, Kritee; Singh, Shubham; Sharma, Sachin; Bhosale, Rashmi S.; Choudhury, Rahul; Masal, Dattatraya P.; Manocha, Alzu; Dhamale, Bhushan Dilip; Khan, Naseem; Asokachandran, Vivekanand; Sharma, Pooja; Ikeh, Melanie; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2022)
Mycobacterium tuberculosis (Mtb) endures a combination of metal scarcity and toxicity throughout the human infection cycle, contributing to complex clinical manifestations. Pathogens counteract this paradoxical dysmetallostasis by producing specialized metal trafficking systems. Capture of extracellular metal by siderophores is a widely accepted mode of iron acquisition, and Mtb iron-chelating siderophores, mycobactin, have been known since 1965. Currently, it is not known whether Mtb produces zinc scavenging molecules. Here, we characterize low-molecular-weight zinc-binding compounds secreted and imported by Mtb for zinc acquisition. These molecules, termed kupyaphores, are produced by a 10.8 kbp biosynthetic cluster and consists of a dipeptide core of ornithine and phenylalaninol, where amino groups are acylated with isonitrilecontaining fatty acyl chains. Kupyaphores are stringently regulated and support Mtb survival under both nutritional deprivation and intoxication conditions. A kupyaphore-deficient Mtb strain is unable to mobilize sufficient zinc and shows reduced fitness upon infection. We observed early induction of kupyaphores in Mtb-infected mice lungs after infection, and these metabolites disappeared after 2 wk. Furthermore, we identify an Mtb-encoded isonitrile hydratase, which can possibly mediate intracellular zinc release through covalent modification of the isonitrile group of kupyaphores. Mtb clinical strains also produce kupyaphores during early passages. Our study thus uncovers a previously unknown zinc acquisition strategy of Mtb that could modulate host-pathogen interactions and disease outcome.
Keywords: metallophore; nutritional immunity; tuberculosis; zinc

Ready access to densely substituted furans using Tsuji-Wacker type cyclization - Masal, Dattatraya P.; Choudhury, Rahul; Singh, Aman; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2022)
A competent method for the construction of highly substituted furans catalyzed by Pd(II) and Cu(II) chloride has been developed. The method provides easy access to di-, tri-, and tetrasubstituted furans from corresponding diols with relatively mild conditions in a unified strategy. The developed method has been successfully tested with more than 25 substrates, which resulted in furans of multiple substitution patterns with up to 84% isolated yields.

Comprehensive study on solomonamides: total synthesis, stereochemical revision, and SAR studies toward identification of simplified lead - Jachak, Gorakhnath R.; Kashinath, K.; Vasudevan, N.; Athawale, Paresh R.; Choudhury, Rahul; Dange, Santoshkumar S.; Agarwal, Heena; Barthwal, Manoj Kumar; Reddy, D. Srinivasa (Journal of Organic Chemistry, 2023)
Solomonamides, a pair of macrocyclic peptide natural products originating from marine sources, have garnered significant attention within the synthetic community owing to their marked anti-inflammatory efficacy and intricate molecular architectures. In this paper, we present a very detailed investigation into solomonamides, including the challenges associated with the total synthesis, the evolution of our synthetic strategies, structural reassignment, synthesis of all possible stereoisomeric macrocycles, biological assessment, structure-activity relationship (SAR) studies, etc. Within the ambit of this total synthesis, diverse strategies for macrocyclization were rigorously explored, encompassing the Friedel-Crafts acylation, cyclization involving the aniline NH2 moiety, macrolactamization utilizing Gly-NH2, and Heck macrocyclization methodologies. In addition, an array of intriguing chemical transformations were devised, including but not limited to photo-Fries rearrangement, Wacker oxidation, ligand-free Heck macrocyclization, oxidative cleavage of indole, synthesis of contiguous stereocenters via substrate/reagent-controlled protocols, and simultaneous making and breaking of olefinic moieties. The findings of this investigation revealed a structurally simplified lead compound. Remarkably, the lead compound, while possessing structural simplification in comparison to the intricate solomonamide counterparts, demonstrates equipotent in vivo anti-inflammatory efficacy.

Total synthesis and absolute configuration determination of the α-glycosidase inhibitor (3S,4R)-6-Acetyl-3-hydroxy-2,2-dimethylchroman-4-yl (Z)-2-Methylbut-2-enoate from Ageratina grandifolia - Dandawate, Monica; Choudhury, Rahul; Krishna, Gamidi Rama; Reddy, D. Srinivasa (Journal of Natural Products, 2023)
Herein, we report the first total synthesis of & alpha;-glycosidaseinhibitor (3R, 4S)-6-acetyl-3-hydroxy-2,2-dimethylchroman-4-yl(Z)-2-methylbut-2-enoate as well as its enantiomer.Our synthesis confirms the chromane structure separately proposedby Navarro-Vazquez and Mata, on the basis of DFT computations. Furthermore,our synthesis allowed us to determine the absolute configuration ofthe natural compound as (3S, 4R)and not (3R, 4S).

Total synthesis and revision of stereochemistry of a natural benzo[g]isochromene stereodiad isolated from rubia philippinensis - Choudhury, Rahul; Miriyala, Satya Ravi Teja; Resmi, K. R.; Sridhar, Balasubramanian; Kasa, S. R. Krishna Murthy; Reddy, D. Srinivasa (Organic Letters, 2024)
This study presents a total synthesis and revision of the stereochemical configuration of the conformationally flexible natural product benzo[g]isochromene stereodiad alongside its diastereomeric counterparts. The highlights of the synthesis are the TiCl4-mediated diastereoselective aldol reaction, Pd-catalyzed lactonization, and Schmidt glycosidation. Our efforts using total synthesis disclosed herein proved that a previously assigned structure required revision.

Enzymatic pathway for kupyaphore degradation in mycobacterium tuberculosis: mechanism of metal homeostasis and turnover - Bhosale, Rashmi S.; Chakraborty, Arnab; Wong, Tsung-Yun; Masal, Dattatraya P.; Choudhury, Rahul; Srivastava, Sonali; Reddy, D. Srinivasa; Aldrich, Courtney C.; Kamat, Siddhesh S.; Mohanty, Debasisa; Gokhale, Rajesh S. (ACS Chemical Biology, 2025)
Metallophores are essential for metal homeostasis, regulating availability, and mediating host-pathogen interactions. Kupyaphores are specialized metallophores produced by Mycobacterium tuberculosis (Mtb) that primarily chelate zinc to support bacterial survival. Elevated kupyaphore levels early in infection highlight their importance, while their rapid decline, despite increasing bacterial loads, indicates tightly regulated mechanisms of production, consumption, and degradation. However, the processes driving kupyaphore catabolism and their role in preventing zinc toxicity in Mtb remain unclear. Here, we show that covalent modification of the isonitrile moiety in kupyaphores releases zinc, triggering degradation through a sequential three-step enzymatic pathway encoded by Mtb. Isonitrile hydratase converts isonitrile groups into formamides, which are subsequently processed into amines by N-substituted formamide deformylase and ultimately oxidized to beta-ketoesters by amine oxidases. The biological significance of this pathway is underscored by the upregulation of these genes under metal-depleted and biofilm-forming conditions. Mutant Mtb strains lacking these genes exhibit impaired growth in metal-limiting environments and reduced levels of biofilm formation. Catalytic intermediates detected in Mtb cultures and infected mouse lung tissues confirm the pathway's in vivo activity. Further, genome mining reveals that similar enzymes are conserved across organisms producing isonitrile-containing metabolites, emphasizing the broader importance of this pathway. Understanding these processes could pave the way for novel therapeutic strategies targeting kupyaphore catabolism.

Peganutonin A: computationally informed synthesis of its revised structure - Saranya, N. Sathya Sai; Choudhury, Rahul; Supekar, Prathmesh R.; Beduru, Srinivas; Williams, Craig M.; Elyashberg, Mikhail E.; Kutateladze, Andrei G.; Bates, Roderick W.; Reddy, D. Srinivasa (Journal of Natural Products, 2025)
The structure of the recently isolated natural product peganutonin A was shown to be incorrect by analysis of the reported spectroscopic data, and therefore, the structure was reassigned utilizing computational methods. Subsequently, the computationally proposed reassignment was confirmed by total synthesis, which was achieved in seven steps from 6-methoxyindole. It is assumed that peganutonin A is not a natural product but an artifact arising from photooxidation of the alkaloid harmaline.

Ready access to benzodiazocines from tryptamines: a druggable scaffold toward antiviral agents - Saranya, N. Sathya Sai; Choudhury, Rahul; Routholla, Ganesh; Supekar, Prathmesh R.; R, Nandhakumaar; Martin, Alna Kuriyickal; Muruganandham, Renuga Devi; Kumar, Bokara Kiran; Reddy, D. Srinivasa (ACS Medicinal Chemistry Letters, 2025)
Herein we report the first synthesis of the proposed structure of a benzodiazocine natural product, peganutonin A. Considering the druggable nature of benzodiazocine and its limited exploration in the field of medicinal chemistry, we generalized the approach and created a library of compounds useful for various biological activities. Key steps in present approach include tryptamine cyclization facilitated by tert-butyl hypochlorite and cleavage of the fused indole ring using ozonolysis. Preliminary screening of the synthesized compounds resulted in potent antiviral compounds against the SARS-CoV-2 virus.
Keywords: Benzodiazocine; drug discovery; Indole cleavage; Lipinski's rule of Five; SARS-CoV-2 inhibition; Tryptamine

Novel routes for bioproduction of delta lactone aroma compounds - Srivastava, Sonali; Chandramouli, Aakash; Gupta, Payal; Manzer, Abdur Rahman; Choudhury, Rahul; Reddy, D. Srinivasa; Yazdani, Syed Shams; Kamat, Siddhesh S.; Mohanty, Debasisa; Nandicoori, Vinay K.; Gokhale, Rajesh S. (Metabolic Engineering, 2026)
Delta lactones are fatty acid-derived aroma compounds that hold tremendous commercial value. As consumer demand for natural flavours continues to rise, the bioproduction of S-lactones, including S-decalactone and S-dodecalactone, is attracting substantial interest. Our study brings forth a novel approach to the bioproduction of S-lactones from glucose, deviating from existing methods that primarily rely on the biotransformation of fatty acids. The high cost of fatty acid raw material constrains the commercial viability of this traditional approach. We engineered surface-lipid producing type I polyketide synthase (PKS) from Mycobacterium smegmatis by incorporating macrolactone thioesterase (TE) domain. Two out of three fusion constructs produced an appropriately engineered PKS-TE fusion protein that facilitated the synthesis of S-lactones. When grown on glucose as the sole carbon source, recombinant E. coli expressing the engineered PKS-TE fusion protein successfully made S-lactones ranging from C8-C18 acyl chains. Our research further highlights the potential of Mycobacterium smegmatis as a cell factory for producing fatty acid-based S-lactones. By genetically designing and engineering Mycobacterium smegmatis to express PKS-TE fusion protein, we achieved bioproduction of various S-lactones. Batch fermentation of the engineered E. coli strain fed with 2 % glucose produced 786 mg/L of S-dodecalactone and 444 mg/L of S-decalactone at 120 h, underscoring the efficacy of our approach. Thus, this study is the first to demonstrate a methodology for redirecting primary metabolic intermediates towards S-lactone biosynthesis in engineered bacteria, enabling the use of inexpensive and renewable feedstocks.
Keywords: Natural flavour; PKS engineering; S-decalactone; S-dodecalactone; S-lactone